2016
DOI: 10.1016/j.jhep.2015.11.029
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic gene HAO2 is downregulated in hepatocellular carcinoma and predicts metastasis and poor survival

Abstract: Our work identifies for the first time the oncosuppressive role of the metabolic gene Hao2. Indeed, its expression is severely decreased in HCC of different species and etiology, and its reintroduction in HCC cells profoundly impairs tumorigenesis. We also demonstrate that dysregulation of HAO2 is a very early event in the development of HCC and it may represent a useful diagnostic and prognostic marker for human HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…The answer may relate to our observation that the set of female-biased genes up-regulated in Ezh1/Ezh2-deficient male liver includes genes that confer protection from HCC in wild-type female liver. One example is Hao2, which is down-regulated in HCC, and its expression inversely correlates with metastasis and survival [70]. Hao2 is strongly induced in E1/E2-KO male liver, but to only ~60% the level of control (wild-type) female liver, and this increase in expression may not be not sufficient to counteract the severe liver injury generated by loss of Ezh1/Ezh2.…”
Section: Discussionmentioning
confidence: 99%
“…The answer may relate to our observation that the set of female-biased genes up-regulated in Ezh1/Ezh2-deficient male liver includes genes that confer protection from HCC in wild-type female liver. One example is Hao2, which is down-regulated in HCC, and its expression inversely correlates with metastasis and survival [70]. Hao2 is strongly induced in E1/E2-KO male liver, but to only ~60% the level of control (wild-type) female liver, and this increase in expression may not be not sufficient to counteract the severe liver injury generated by loss of Ezh1/Ezh2.…”
Section: Discussionmentioning
confidence: 99%
“…Several abnormal lipid metabolism factors are partially remedied by troxerutin treatment. For example, the synthesis of long chain fatty acids and the inhibition of fatty acid oxidation are the main mechanism of renal lipotoxicity associated with Acaca, Fasn, Hao2, and Acaa1b (65,66). Cyp4a10 can respond to increased catalase, intensifying aberrant lipid metabolism (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is likely that the enhanced expression of this gene is specific for cells addressed to cancer progression and that the primary role of PPP induction is to maintain the redox equilibrium in preneoplastic cells, whereas pentoses can also be generated by the non-oxidative phase of PPP in a G6PD-independent manner [6]. Accordingly, we recently found that intracellular ROS levels are increased in tumorigenic cells compared to the non-tumorigenic counterpart [37]. In this context, it should be noted that the activation of NRF2/KEAP1 transcriptional pathway may play a critical role in G6PD increase.…”
Section: Discussionmentioning
confidence: 99%